Pengaruh Media Audio Visual Melalui Platform Youtube Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Matematika Kelas IV di SD Negeri 4 Pemenang Barat Tahun Pelajaran 2023/2024 - Zazrin, Zazrin; Marzoan, Lalu (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2025)
In this research, a pre-experimental group pretest-posttest type 1 design and quantitative methodology were used. The aim of this research is to find out whether fourth grade students at SD Negeri 1 Juara Barat for the 2023–2024 academic year can improve their mathematics learning outcomes by using audio-visual material found on YouTube. The primary data source for collecting data for this research is the results of students' pretest and posttest. Then it was researched using quantitative descriptive and inferential analysis using the SPSS 16 program. For this research, thirty fourth grade students from one group in the experimental class were used as samples. To obtain research results, the Paired Sample T test from SPSS 16 was used. The researcher's analysis of the pretest and posttest results produced a significance value of 0.00 using the paired sample t test in SPSS 16. As a result, there was a difference of <0.05 between the pretest and posttest findings. Thus, it can be concluded that students' mathematics learning outcomes improve after studying with audio-visual sources available on the YouTube platform. Specifically Ha is accepted but H0 is rejected.